HAK KARYAWAN YANG TERDAMPAK PEMUTUSAN HUBUNGAN KERJA SECARA SEPIHAK DI PT. YOUNG TREE INDUSTRIES - Aden Fadli Mukhammad; Rosalinda Elsina Latumahina (Gapenas Publisher, 2023)
Termination of employment or what is often called layoffs is the end of an employment relationship betweeniworkers or laborersiand employersiwhere theiend ofian employmentirelationship resultsiin theiloss ofithe obligations andirights ofiworkers. Layoffs are often carried out by a company where a situation occurs which results in a reduction in workers so that the company can survive its operations. Workers who experience layoffs also have their own legal protection for the rights and obligations that must be given by the company because it has laid off its workers/laborers.Theimethod used inithis studyiis ainormative juridicalimethod withia statutory and conceptual approachiwhich will discuss inidetail what are theilegal protections for employees who experience layoffs and what are the rights of employees when laid offiby theicompany. Theiresults ofithis studyiare thatimany companies carry out layoffs of workers arbitrarily without giving the rights that workers must receive when laid off. The existence of a rule in the law also cannot guarantee whether a company can fulfill certain rights and obligations to workers who have been laid off. With unilateral layoffs by companies, it can also increase the unemployment rate in this country, therefore strengthening laws and regulations is also one way so that companies do not arbitrarily lay off workers unilaterally